The impact of an educational video about the role of an emergency nurse, viewed by emergency nurses' support systems, on emergency nurses' wellbeing. (December 2022) - Nevill, Alexandra; Pristupa, Kathryn; O'Reilly, Gerard
Abstract: Background: High stress daily events contribute to burnout in emergency nurses. Strong and informed support systems are essential in ensuring emergency nurses are actively dealing with their workplace-generated stress, through informal social support. Methods: A pre and post intervention design over a 6-month period in a single ED. A video was created by emergency nurses to orientate their support system to their role and work environment. Its impact on nurse well-being was assessed. Results: More than half of the participants considered their spouse/partner to be their main support system (n = 52, 58%). The majority of participants found their support system: (i) had a greater understanding of their everyday work (n = 79, 88%), (ii) were more engaged when talking about work (n = 72, 80%), (iii) asked more questions about work (n = 63, 70%), and (iv) reported they had an improved ability to debrief with their support system (n = 67, 74%). The median total World Health Organization wellbeing score improved by two points (7%, p < 0.001). Conclusion: Emergency nurses' support systems had a greater understanding of the emergency nurse's role and work environment following exposure to the video. This in turn improved the emergency nurses' ability to debrief at home, experience of support, and ultimately their wellbeing.